Pentecostalism : the world their parish - Martin, David, 1929-2019. (Oxford ; Malden, Mass. : Blackwell Publishers, 2002)
This volume deals with the largest global shift in religion over the last 40 years, the rise of Pentecostalism and charismatic Christianity. It examines the widely differing forms of Pentecostal religion across the five continents
A cultural revolution : sources, character, niches -- North America and Europe : contrasts in receptivity -- Latin America : a template? -- Latin America : ambiguity in different cultural sectors -- Indigenous peoples -- Africa -- Asia -- Trying conclusions : a global option?
Includes bibliographical references (pages 192-193) and index
Keywords: Pentecostalism